1997
DOI: 10.1007/s004140050100
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the stability of benzodiazepines in blood and plasma stored at 4° C

Abstract: An approach to determine the stability of benzodiazepines and some of their metabolites (n = 13) by means of a routinely applied gas chromatographic method using electron capture detection was made in this preliminary study. Validation data of the method are given. Spiked blood and plasma samples were stored at 4 degrees C and analysed at selected times up to 240 days. The concentrations of all analytes had decreased to at least 60% of the original levels at the end of the observation period. A clear pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…The concentration of all other compounds had decreased to at least 60% of the initial concentration. Neither protein binding nor partition into erythrocytes allowed a conclusive explanation of the different degradation rates (Skopp et al 1999). Even when stored at -20°C for a time period of 1 year, a decrease between 10% and 20% of the starting concentration could be observed for five benzodiazepine-type drugs (El Mahjoub and Staub 2000).…”
Section: Stability Of Major Drugs and Potential Artefacts In Urine Comentioning
confidence: 96%
“…The concentration of all other compounds had decreased to at least 60% of the initial concentration. Neither protein binding nor partition into erythrocytes allowed a conclusive explanation of the different degradation rates (Skopp et al 1999). Even when stored at -20°C for a time period of 1 year, a decrease between 10% and 20% of the starting concentration could be observed for five benzodiazepine-type drugs (El Mahjoub and Staub 2000).…”
Section: Stability Of Major Drugs and Potential Artefacts In Urine Comentioning
confidence: 96%
“…In terms of potentially putrefaction caused changes, there was no significant loss until 3 months of storage at 25°C [54]. A study published in 1998 showed that unpreserved blood spiked with 13 benzodiazepines (including metabolites) stored at 4°C decreased in concentration over a period of 240 days, with several analytes being undetected after 60 days [55]. Another study was performed looking at the stability of benzodiazepines in unpreserved whole blood at room temperature, 4, -20 and -80°C, with the optimal storage temperature being -80°C, followed closely by -20°C, Fig.…”
Section: Benzodiazepinesmentioning
confidence: 99%
“…whole blood, plasma, serum and/or urine), aliquoted and stored at the same time and in the same way as ordinary samples. The concentrations are measured at selected time intervals and compared to detect any trend regarding degradation [29][30][31][32][33][34][35][36][37][38][39][40]. Among reported investigations, also studies on authentic material from volunteers dosed with the drug or from laboratory cases have been performed [33,[40][41][42][43][44].…”
Section: Design and Evaluation Of Stability Experimentsmentioning
confidence: 99%
“…Specific stability studies of several forensically important drugs in blood and other fluids or tissues have been published including cocaine, its metabolites and its degradations product in whole blood, post-mortem blood or plasma [32,37,45,46], benzodiazepines, antidepressants, antipsychotics, analgesics and/or hypnotics in whole blood, plasma or post-mortem blood [29,30,43,[47][48][49][50][51], morphine and/or its glucuronides and/or buprenorphine in whole blood, plasma or post-mortem blood [31,33,52], 11-nor-Δ 9 -carboxy-tetra-hydrocannabinol glucuronide (THCCOOglu) in plasma [38,53], toluene and acetone in liver, brain and lungs [39], 3,4-methylenedioxymethamphetamine (MDMA), 3,4-methylenedioxyethylamphetamine (MDEA) and 3,4-methylene-dioxyamphetamine (MDA) in whole blood [34], carbon monoxide in post-mortem blood [54], GHB in blood, serum or post-mortem blood [44,55,56] and ethanol in whole blood, plasma, post-mortem blood or vitreous humor [40,57,58].…”
Section: Stability Investigations Of Drugs In Biological Specimensmentioning
confidence: 99%
See 1 more Smart Citation